2020
DOI: 10.1101/2020.03.13.20035329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence factors of death risk among COVID-19 patients in Wuhan, China: a hospital-based case-cohort study

Abstract: In this hospital-based case-cohort study, we found that serum urea nitrogen, TBIL, LDH and AST/ALT ratio, several markers of extrapulmonary organ injuries, were positively correlated with death risk of COVID-19 patients. We provide evidence for the first time that multiple organ damage on admission influences the prognosis of COVID-19 patients. Early hospitalization is beneficial for elevating the survival rate of COVID-19 patients especially critical ill patients. AbstractBackground. Coronavirus disease 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 15 publications
8
77
0
Order By: Relevance
“…Accumulating data indicate that SARS-CoV-2 infection causes multiple organ injuries, such as lymphopenia, myocardial dysfunction and acute renal failure [9,[15][16][17]25]. In the present study, we showed that oxygenation index, an index of respiratory function, was positively correlated with serum albumin.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Accumulating data indicate that SARS-CoV-2 infection causes multiple organ injuries, such as lymphopenia, myocardial dysfunction and acute renal failure [9,[15][16][17]25]. In the present study, we showed that oxygenation index, an index of respiratory function, was positively correlated with serum albumin.…”
Section: Discussionsupporting
confidence: 61%
“…The present study aimed to analyze SARS-CoV-2-induced ALI, its association with death risk and the prognosis after discharge. The major findings of this study include: (1) ALI is more common in the critically ill COVID-19 patients; (2) Accumulating data demonstrated that SARS-CoV-2 infection caused multiple organ injuries, including myocardial dysfunction, lymphopenia and even acute renal failure [15][16][17]. In the present study, we described ALI among COVID-19 patients.…”
Section: Discussionsupporting
confidence: 51%
“…Evidence pointing to the person-to-person transmission has occurred among close contacts in hospital and family [6]. As reported by other researchers and our team found that patients with COVID-19 present primarily with fever, diarrhea, fatigue, dry cough, lymphopenia and radiographic evidence of pneumonia [7][8][9]. The Chinese Center for Disease Control and Prevention recently revealed that the death risk of mild COVID-19 patients was relatively low in a large Chinese population-based study, the fatality rate was signi cantly elevated among critical ill COVID-19 cases [10].…”
Section: Introductionsupporting
confidence: 61%
“…Among a variety of recent publications about COVID-19, accumulated evidence suggests that SARS-CoV-2 infections might cause multiple and systemic injuries, including acute renal failure, myocardial dysfunction, and acute liver injury 20,24,25 . Additionally, there are recent studies analyzing COVID-19 patients in detail with respect to liver enzymes, such as ALT and AST 20,26 .…”
Section: Discussionmentioning
confidence: 99%